Isolation and molecular identification of carbohydrase and protease producing Bacillus subtilis JCM 1465 isolated from Penen Hot Springs in North Sumatra, Indonesia - Edy Fachrial; Sari Anggraini; Harmileni; Titania T Nugroho; Saryono (Society for Indonesian Biodiversity, 2019)
Abstract. Fachrial E, Anggraini S, Harmileni, Nugroho TT, Saryono. 2019. Isolation and molecular identification of carbohydrase and protease producing Bacillus subtilis JCM 1465 isolated from Penen Hot Springs in North Sumatra, Indonesia. Biodiversitas 20: 3493-3498. The application of enzymes industrially is increasing every year and thermophilic microbes are a promising source of these enzymes for industrial use due to their temperature stability. The aim of this study, therefore, was to isolate, characterize and identify the enzyme producer-thermophilic bacteria from the Penen Hot Spring in Deli Serdang, North Sumatra, Indonesia. In the experimental setup, carbohydrase activities including inulinase and amylase were determined by the formation of clear zone around the colonies after soaking with Lugol on the TSA medium supplemented with 1% inulin powder and 1% starch. Similarly, the protease activities were determined by the formation of clear zone around the colonies on Skim Milk Agar Medium. Then, of the 11 isolates, only one known as UTMP 12 showed maximum enzyme activity. The isolate was then characterized based on morphology and biochemistry and found to be Bacillus subtilis strain JCM 1465 (accession number NR_113265, homolog 99.72%). Furthermore, this is the first study on carbohydrase and protease activities of Bacillus subtilis strain JCM 1465 and the result shows that the thermophilic bacteria are needed in the production of carbohydrase and protease.